Kemampuan Literasi Matematika Peserta Didik Kelas IX berdasarkan Gaya Belajar menurut David Kolb - Furqon, Syifa'ul; Siswanah, Emy; Tsani, Dyan Falasifa (Edumatica : Jurnal Pendidikan Matematika, 2021)
The purpose of this study was to determine the characteristics of mathematical literacy skills of class IX students based on learning styles according to David Kolb. This study uses an analytical descriptive approach with research subjects of class IX A students of SMP 4 Pemalang in the academic year 2019/2020. The results of the study stated that High, Medium and Lower Diverger Subjects were able to solve math literacy problems level 2, 3 and 5. The Upper Assimilator Subject was able to solve math literacy problems level 2, 3, 4, 5 and 6. The Middle Assimilator was complete at levels 2, 3, 5 and 6. The Lower Assimilator Subject is only completed at levels 2, 3, and 5. The Upper Converger Subject is able to complete level 2, 3, 4, 5, and 6 mathematics literacy. less able at level 3. Lower Converger is complete at level 2 and 3 then less able at level 4. Upper Accomodator subject is able to solve mathematical literacy problems level 3, 4, 5, and 6 then less able at level 2. Middle Accomodator is complete at level 2 and 3. whereas Lower Accommodation is only able to solve level 2 problems and less able to solve level 3 mathematical literacy problems.